THE INFLUENCE OF EMOTIONAL INTELLIGENCE ON JOB STRESS MEDIATED BY SOCIAL SUPPORT AMONG FEMALE TEACHERS AT SMAN 8 PADANG - Febi Marliza; Yuki Fitria (Universitas Nusa Cendana, 2025)
This study aims to analyze the effect of emotional intelligence on job stress with social support as a mediating variable among female teachers at SMAN 8 Padang. Using a quantitative approach with a descriptive-causal design, data were collected through questionnaires distributed to 52 respondents using a total sampling technique. Descriptive analysis revealed that emotional intelligence was in the moderate category, while job stress was in the moderately low category Inferential analysis using SEM-PLS showed that emotional intelligence had a significant negative effect on job stress, emotional intelligence had a significant positive effect on social support, and social support had a significant negative effect on job stress. Additionally, social support significantly mediated the relationship between emotional intelligence and job stress. These findings highlight the importance of strengthening emotional and social aspects to reduce job stress in educational environments. The limitation of this study lies in the narrow sample scope, which only includes one school, making the results less generalizable. Keywords: Emotional Intelligence; Job Stress; Social Support; Female Teachers